The whiteboard: visualising personal agency in a lockdown microcosm. Issue 1 (1st January 2023) - O'Callaghan, Simone
Abstract : This visual-essay is based in the domestic space during Covid-19 lockdown in NSW, Australia, from 24 March to 25 May 2020. It is an auto-ethnographic documentation of how one family managed living with ADHD under lockdown. Assumptions and stereotypes about ADHD are broken down and challenged in the supporting narrative. These explain the complexity of living with ADHD and illustrate how very small, seemingly insignificant acts can have a large impact on managing the compounding effect an unprecedented situation like lockdown, on issues prevalent in those with ADHD such as anxiety, organisation, and lack of control over in personal circumstances. These are framed within the larger context of preceding catastrophic 2019/2020 summer bushfires that occurred in Australia, to provide the reader with insights into the emotional states in which many people in Australia entered lockdown. The author invites the reader to pay attention to the details of each of these images, to observe the visual communication cues that appear on the whiteboards, such handwriting by different people, doodles, illustrations, colour coding, and the layout that evolved over time, as personal agency within the family members developed.